2001
DOI: 10.1017/s0048577201991504
|View full text |Cite
|
Sign up to set email alerts
|

Missed prime words within the attentional blink evoke an N400 semantic priming effect

Abstract: When subjects identified a target among distractors in a rapid serial visual presentation task, the detection of a subsequent target is impaired (attentional blink). By measuring event-related potentials (ERPs) we investigated if the processing of an unidentified prime word elicits the N400 semantic priming effect. Subjects (N = 12) had to identify three target words among distractors in a rapid serial visual presentation task. We varied the association strength between a prime (second target) and a probe (thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 20 publications
(21 reference statements)
8
97
1
Order By: Relevance
“…These authors tested this suggestion within the attentional blink paradigm (Raymond, Shapiro, & Arnell, 1992) which produces changes in attention at late processing levels (Rolke, Heil, Streb, & Hennighausen, 2001). As in the study of Yeshurun and Levy (2003), participants performed either a spatial or a temporal gap discrimination task.…”
Section: Discussionmentioning
confidence: 99%
“…These authors tested this suggestion within the attentional blink paradigm (Raymond, Shapiro, & Arnell, 1992) which produces changes in attention at late processing levels (Rolke, Heil, Streb, & Hennighausen, 2001). As in the study of Yeshurun and Levy (2003), participants performed either a spatial or a temporal gap discrimination task.…”
Section: Discussionmentioning
confidence: 99%
“…Neely (1991) has shown that the semantic priming effect could be subserved by multiple mechanisms, including automatic spreading activation and strategically controlled processes of expectancy priming and semantic matching/ integration. The semantic priming effects elicited by the primers may involve non-equivalent mechanisms; it is possible that the measurement of RT was not precise enough to differentiate between these mechanisms (Heil et al, 2004;Neely and Kahan, 2001;Rolke et al, 2001).…”
Section: Semantic Style-match Judgmentsmentioning
confidence: 99%
“…In trials with successful report of both targets, each target produces a positively peaking evoked response potential (ERP) occurring approximately 300 ms after target onset (Luck et al 1996;McArthur et al 1999)-a so-called P300 (Donchin 1981). Interestingly, however, this P300 component has been found to be largely or completely suppressed in trials where T2 is ''blinked'', hence, cannot be reported (Dell'Acqua et al 2003;Kranczioch et al 2003;Luck et al 1996;McArthur et al 1999;Rolke 2001;Vogel and Luck 2002). Comparable observations could be made in MEG analyses, where M300, the magnetic equivalent of the P300, is also attenuated or even suppressed in blink trials (Kessler et al 2005a;Shapiro et al, submitted).…”
Section: A Neurocognitive Scenariomentioning
confidence: 99%